2001
DOI: 10.1038/sj.bmt.1703028
|View full text |Cite
|
Sign up to set email alerts
|

Decitabine with allogeneic peripheral blood stem cell transplantation in the therapy of leukemia relapse following a prior transplant: results of a phase I study

Abstract: Summary:Relapse after allogeneic progenitor cell transplant is associated with a poor prognosis for patients with advanced leukemia, with few curative options available. Use of novel chemotherapeutic agents with limited toxicity is warranted. We investigated the role of decitabine, a pyrimidine analogue with significant anti-leukemic effect and limited toxicity, in this setting. Fourteen patients with advanced acute leukemia or transformed chronic myelogenous leukemia (CML) who had failed previous allogeneic t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
15
0

Year Published

2002
2002
2014
2014

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 40 publications
(15 citation statements)
references
References 15 publications
(21 reference statements)
0
15
0
Order By: Relevance
“…Other factors that have been reported to impact the outcome after the second transplant are the absence of aGVHD at the time of second HSCT, 5,23 remission status at second transplant, 6,20,21 using a female donor, 13 development of chronic GVHD after the second HSCT, 23 and source of stem cells. 24 Al-Qurashi et al 25 and Eapen et al 22 did not find any advantage to using a different donor for the second transplant procedure.…”
Section: Discussionmentioning
confidence: 99%
“…Other factors that have been reported to impact the outcome after the second transplant are the absence of aGVHD at the time of second HSCT, 5,23 remission status at second transplant, 6,20,21 using a female donor, 13 development of chronic GVHD after the second HSCT, 23 and source of stem cells. 24 Al-Qurashi et al 25 and Eapen et al 22 did not find any advantage to using a different donor for the second transplant procedure.…”
Section: Discussionmentioning
confidence: 99%
“…19,59 Santourlidis et al 60 reported that treatment with DNAdemethylating agents results in rapid and stable induction of transcription and cell surface expression of formerly unexpressed KIRs (killer Ig-like receptors) in natural killer cells that are involved in the specific recognition of leukemic target cells and are able to generate a GVL effect. Furthermore, treatment with low-dose azacytidine is associated with only marginal non-hematopoietic toxicity.…”
Section: 55mentioning
confidence: 99%
“…Other factors reported to be associated with outcome after second allo-SCT are remission status at the time of second transplant; 12,13,17,18 using a female donor; 19 development of GVHD after the second allo-SCT; 20,21 and the source of stem cells. 22 Leukemia burden at the time of first transplantation is considered to be a bad prognostic factor.…”
Section: Second Allo-sctmentioning
confidence: 99%
“…11,12 Measures to enhance the therapeutic index of DLI by the addition of IL-2 13 or low-dose cytarabine (LD-AraC) combined with GM-CSF 14 have not shown a consistent improvement. To use the particular mechanisms of action of DNA demethylating agents within the transplant setting, decitabine had been incorporated into the treatment of patients before allografting 15,16 and 5-azacytidine treatment followed by DLI has recently been described for a patient relapsed after allografting for MDS. 17 However, the optimal dose of a hypomethylating agent in this setting, where hematopoiesis may be much more sensitive to the myelotoxicity mediated sometimes by even low doses of the drugs, has not yet been established.…”
Section: Introductionmentioning
confidence: 99%